1999
DOI: 10.1006/acha.1999.0236
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Compactly SupportedM-Band Wavelets

Abstract: In this paper, we consider the asymptotic regularity of Daubechies scaling functions and construct examples of M-band scaling functions which are both orthonormal and cardinal for M ¢ 3. ᭧ 1999 Academic Press

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…For M ≥ 3 and N ≥ 1, similar scaling function with minimal support, which we denoted by φ M,N , was constructed in [8]. It was shown that φ M,N is just the Haar function for N = 1 (hence symmetric for N = 1), has asymptotic Hölder regularity proportionally to ln(sin Mπ/(2M + 2)) −1 (ln M) −1 N for even M and to (4 ln M) −1 ln N for odd M as N tends to infinity [2,11,13], and has explicit expression if N ≤ M − 1 [3,14]. In this note, we show that the M-band scaling function φ M,N with minimal support is asymmetric for N ≥ 2.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…For M ≥ 3 and N ≥ 1, similar scaling function with minimal support, which we denoted by φ M,N , was constructed in [8]. It was shown that φ M,N is just the Haar function for N = 1 (hence symmetric for N = 1), has asymptotic Hölder regularity proportionally to ln(sin Mπ/(2M + 2)) −1 (ln M) −1 N for even M and to (4 ln M) −1 ln N for odd M as N tends to infinity [2,11,13], and has explicit expression if N ≤ M − 1 [3,14]. In this note, we show that the M-band scaling function φ M,N with minimal support is asymmetric for N ≥ 2.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Our construction can be compared with the one carried out by Chui and Lian in [6], which led to 3-band orthonormal symmetric-antisymmetric wavelets with possibly arbitrarily high regularity and also to two recent constructions of families of M-band wavelets by Belogay and Wang [2] and by Bi et al [3]. However, all these constructions were carried out in the orthogonal case and suffer some of the drawbacks of that setting.…”
Section: Introductionmentioning
confidence: 86%
“…As explained before, we can consider the restrictions 3 From this one easily deduces that the spectral radius of 3 T |P a | 2 | F 2 , and hence of 3 T |P a | 2 , is…”
Section: Regularity Of Burt-adelson 3-band Waveletsmentioning
confidence: 95%
See 2 more Smart Citations